Structural, Optical Constants and Photoluminescence of ZnO Thin Films Grown by Sol-Gel Spin Coating - Abdel-Sattar Gadallah; M. M. El-Nahass (Advances in Condensed Matter Physics)
We report manufacturing and characterization of low cost ZnO thin films grown on glass substrates by sol-gel spin coating method. For structural properties, X-ray diffraction measurements have been utilized for evaluating the dominant orientation of the thin films. For optical properties, reflectance and transmittance spectrophotometric measurements have been done in the spectral range from 350 nm to 2000 nm. The transmittance of the prepared thin films is 92.4% and 88.4%. Determination of the optical constants such as refractive index, absorption coefficient, and dielectric constant in this wavelength range has been evaluated. Further, normal dispersion of the refractive index has been analyzed in terms of single oscillator model of free carrier absorption to estimate the dispersion and oscillation energy. The lattice dielectric constant and the ratio of free carrier concentration to free carrier effective mass have been determined. Moreover, photoluminescence measurements of the thin films in the spectral range from 350 nm to 900 nm have been presented. Electrical measurements for resistivity evaluation of the films have been done. An analysis in terms of order-disorder of the material has been presented to provide more consistency in the results.